Costs of Public Pharmaceutical Services in Rio de Janeiro Compared to Farmácia Popular Program - Rondineli Mendes da Silva; Rosângela Caetano
ABSTRACT OBJECTIVE To analyze the costs of public pharmaceutical services compared to Farmácia Popular Program (Popular Pharmacy Program). METHODS Comparison between prices paid by Aqui Tem Farmácia Popular Program (Farmácia Popular is available here) with the full costs of medicine provision by the Municipal Health Department of Rio de Janeiro. The comparison comprised 25 medicines supplied by both the municipal pharmaceutical service and Aqui Tem Farmácia Popular Program. Calculating the cost per pharmaceutical unit of each medicine included expenditure by Municipal Health Department of Rio de Janeiro with procurement (price), logistics, and local dispensation. The reference price of medicines paid by Aqui Tem Farmácia Popular was taken from the Brazilian Ministry of Health standard in force in 2012. Comparisons included full reference price; reference price minus 10.0% copayment by users; and maximum reference paid by the Ministry of Health (minus copayment and taxes). Simulations were carried out of the differences between the costs of Municipal Health Department of Rio de Janeiro with the common medicines and those potentially incurred based on the reference price of Aqui Tem Farmácia Popular. RESULTS The Municipal Health Department of Rio de Janeiro spent R$28,526,526.57 with 25 medicines of the common list in 2012; 58.7% accounted for direct procurement costs. The estimated costs of the Health Department were generally lower than the reference prices of the Aqui Tem Farmácia Popular Program for 20 medicines, regardless of reference prices. The potential costs incurred by Health Department if expenditure of its consumption pattern were based on the reference prices of Aqui Tem Farmácia Popular would be R$124,170,777.76, considering the best scenario of payment by the Brazilian Ministry of Health (90.0% of the reference price, minus taxes). CONCLUSIONS The difference in costs between public provision by Municipal Health Department of Rio de Janeiro and Farmácia Popular Program indicates that some reference prices could be reviewed aiming at their reduction.